Manajemen pembangunan wilayah Jabodetabek - Najmulmunir, Nandang (Jakarta, Indonesia : Madani Institute, 2011)
City planning of Jakarta metropolitan area related to the planning of cities in Jawa Barat as urban areas surrounding the metropolitan city of Jakarta.
Includes bibliographical references.
Keywords: City planning -- Indonesia -- Jakarta Raya; Metropolitan areas -- Indonesia -- Jakarta Raya; Cities and towns -- Indonesia -- Jawa Barat